The Distribution of Body Weight Force on Toe and Heel before and after Exercise Therapy in Children with Spastic Diplegia Cerebral Palsy - Keyvan Sharif-Moradi; Nader Farah-Pour; Mohammad Sadegh Saba; Nosratollah Farajollahi (University of Social Welfare and Rehabilitation Sciences, 2005)
Objective: The purpose of this study was to assess the distribution of body weight force on toe and heel before and after exercise therapy and its effects on relaxation of children with spastic diplegia cerebral palsy. Materials & Methods: Ten children with spastic diplegia cerebral palsy between 8 to15 years of age participated in this study. Their mean weight and height were (30.8kg ± 5.7kg) and (1.35m±0.09m) respectively. Subjects underwent a 12 weeks of exercise therapy. A dynamic stability platform system (BIODEX) was used to measure the mean percentage of body weight pressure on toe and heal. The balance tests were repeated on stable, almost stable and unstable base of support as well as with and without shoes. Results: Showed that the mean percentage of body weight pressure on toe and heal after exercise therapy was not significant (p>0.05). The mean percentage of body weight pressure on toe and heal was significantly decrease after exercise therapy in both with and without shoes (p<0.05). The greatest improvement achieved on almost stable and unstable conditions. Wearing shoes resulted in a balance percentage of body weight pressure on toe and heal on stable situation of stability platform the percentage of body weight pressure on toe and heal has no difference before and after exercise therapy. After exercise therapy strengthening the muscle of the ankle joint balance the percentage of body weight pressure on toe and heal. Wearing shoes decrease the muscle stretch and therefore balance the percentage of body weight pressure on toe and heal. Conclusion: The flexibility of spastic muscle and strengthening of the relax muscle must be perform. This result provides good information for physician in recognizing and therapy impacts on cerebral palsy children.